Short-Term Outcomes of Refractory Diabetic Macular Edema Switch From Ranibizumab to Dexamethasone Implant and the Influential Factors: A Retrospective Real World Experience - Hsia, Ning-Yi; Lin, Chun-Ju; Chen, Huan-Sheng; Chang, Cheng-Hsien; Bair, Henry; Lai, Chun-Ting; Lin, Jane-Ming; Chen, Wen-Lu; Tien, Peng-Tai; Wu, Wen-Chuan; Tsai, Yi-Yu (Frontiers in Medicine, 2021)
Introduction: To evaluate the effectiveness and safety of intravitreal dexamethasone (DEX) implants in refractory diabetic macular edema (DME) treated by intravitreal ranibizumab. Materials and Methods: We retrospectively analyzed DME patients who received DEX implant treatment after being refractory to at least three monthly intravitreal ranibizumab injections. The main outcomes were best-corrected visual acuity (BCVA), central retinal thickness (CRT), and intraocular pressure (IOP). Results: Twenty-nine eyes of 26 patients who had previously received an average of 8.1 ± 4.4 ranibizumab injections were included. Patients received between one and three DEX implants during 12.4 ± 7.4 months of follow-up. The mean final CRT significantly decreased from 384.4 ± 114.4 μm at baseline to 323.9 ± 77.7 μm (p = 0.0249). The mean final BCVA was 51.4 ± 21.3 letters, which was not significant compared to baseline (44.9 ± 30.2 letters, p = 0.1149). Mean IOP did not increase significantly. All patients tolerated the treatment well without serious adverse events. Higher baseline CRT and worse BCVA correlated with better therapeutic responses. Conclusion: Switching to DEX implant is feasible and safe for treating patients of DME refractory to intravitreal ranibizumab in real world. Further larger-scale or multicenter studies would be conducted to explore different DEX treatment strategies for DME, such as first-line or early switch therapy, for better BCVA improvement.